Correlates of Ichthyofaunal Diversity With Relation to Environmental Variables of Badigad River, Nepal - Ganesh Bahadur Thapa; Dinesh Singh; Mohsan Raza; Dipak Rajbanshi; Malik Shahzaib Khalid (International Journal of Zoology)
Studying ichthyofauna, and the effect of environmental variables is crucial for conserving aquatic biodiversity, understanding ecosystem dynamics, and promoting sustainable fisheries management. An ichthyological survey was carried out in the Badigad River in the Gulmi and Baglung districts, during the winter months of October through December 2022 and, the summer months of April through June 2023. The fish species collected during the period of study were Anguilla bengalensis bengalensis, Botia geto, Schizothorax richardsonii, Garra gotyla., Barilius barila, Balitora brucei, Garra nasuta, Lepidocephallichthys guntea, Labeo dyocheilus, Neolissochilus hexagonolepis, Crossocheilus latius, Tor tor, Channa orientalis, Pseudecheneis sulcata, and Glyptothorax pectinopterus. The study identified 15 fish species belonging to 4 orders, 6 families, and 14 genera. Schizothorax richardsonii was the most abundant species (34.5%), followed by Garra gotyla (11.11%). Water quality parameters, including temperature (20°C–29°C), dissolved oxygen (7.2–10 mg/L), and pH (7.8–8.3), were within acceptable ranges for fish survival. The number of fishes was greatest in the order Cypriniformes (89.41%), followed by Siluriformes (7.34%), Perciformes (3.5%), and Anguiliformes (0.09%). The fish population has been seen to be declining daily as a result of several issues, including electric fishing, the destruction of brood during spawning season, as well as significant floods, damming, and an unfavorable habitat for the fish composition. The current study provided a baseline assessment of the fish community in the Badigad River.